Consumer Protection in the Banking Credit Agreement in Accordance with the Principle of Proportionality under Indonesian Laws - Dwi Ratna Indri Hapsari; Kukuh Dwi Kurniawan (Universitas Lampung, 2020)
The implementation of the principle of freedom of contract gives rise to the types of agreements not regulated in the law or The Indonesian Civil Code (ICC). We are familiar with the term Standard contract or standard agreement. Standard agreements are often used in the banking world, one of which is in banking credit agreements, as we all understand that the position of the customer is weaker than the bank, so it must be protected by law. In order to protect these interests, the customer is given protection contained in the Banking Act regulations as well as the Consumer Protection Act and its derivative regulations. Specifically, the credit agreement format as the standard agreement set out in Financial Services Authority Circular Number 13 / SEOJK.07 / 2014 Concerning Standard Agreements is that credit agreements that contain rights, obligations and requirements that are legally binding on customers, are required to use letters, writing, symbols, diagrams, signs, terms, readable phrases, and / or sentences simple ones in Indonesian that are easily understood by customers. This is in an effort to provide protection to customers and the regulatory and supervisory functions of the Financial Services Authority.